Evaluation of common variants in CNR2 gene for bone mineral density and osteoporosis susceptibility in postmenopausal women of Han Chinese. Issue 12 (December 2015) - Zhang, C.; Ma, J.; Chen, G.; Fu, D.; Li, L.; Li, M.
Abstract Summary Postmenopausal osteoporosis is a major health problem with important genetic factors in postmenopausal women. We thoroughly evaluated the relationship ofCNR2 polymorphisms with osteoporosis in a cohort of 1032 osteoporosis patients and 2089 healthy controls from Han Chinese postmenopausal women. Statistically significant differences, depending on different genotypes, were presented. Introduction Osteoporosis is a major health problem in postmenopausal women, which is a multifactorial disease in which genetic determinants are modulated by hormonal, environmental, and nutritional factors. An important clinical risk factor in the pathogenesis of osteoporosis is the presence of genetic polymorphism in susceptibility genes. The aim of our study was to investigate whetherCNR2 gene, which attributes to osteoporosis susceptibility in some populations, is associated with bone mineral density (BMD) or osteoporosis in Han Chinese postmenopausal women. Methods We examine 39 SNPs covering the region ofCNR2 gene in 3121 Han Chinese postmenopausal women, consisting of 1032 osteoporosis patients and 2089 healthy controls, to evaluate the association with BMD and osteoporosis. Results We found that rs4237 and rs2501431 were significantly associated with BMD and osteoporosis (correctedp  = 0.020085 and 0.017199) in our sample, and the TT genotype of rs2501431 and the AA genotype of rs4237 had lower lumbar spine BMD and femoral neck BMD compared with the other genotypes. Additionally, analyses by haplotypes indicated that two haplotype blocks, containing rs4237 and rs2501431 respectively, in theCNR2 gene significantly associated with BMD and osteoporosis (both global permutationp  < 0.001), and a risk haplotype (ATTT) in the block of rs3003336-rs2501431-rs2502992-rs2501432 had almost 4-fold increase in the cases. Conclusions Our results provide further supportive evidence for an important role ofCNR2 gene in the etiology of osteoporosis and suggest that it may be a genetic risk factor for BMD and osteoporosis in Han Chinese postmenopausal women.